Implementing Telework Agreement in Slovakia - Zulova, Jana (European Scientific Journal, ESJ, 2017)
The Telework Agreement was signed by the European social partners (ETUC, UNICE/UEAPME and CEEP) on 16 July 2002 after eight months of negotiations. It is an autonomous framework agreement regulated through social dialogue, so it is a form of soft law. The Telework Agreement offers a range of implementation methods which have been used in the Member States. We have followed our national traditions by transposing the telework agreement into legislation. The submitted paper attempts to analyze the national regulatory framework of the status and working conditions of employees performing telework in the Slovak republic and examines how the Slovak legislator approaches the implementation of this phenomenon in the current world of work.